Groundwater Modelling with Limited Data: A Case Study of Yobe River Basin, North East Nigeria - Hassan, M.; Carter, R.C.; Rushton, K.R. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2004)
An exploratory numerical groundwater model of a shallow aquifer interacting with a river in a semi-arid zone was developed using MODFLOW. The model simulated field data adequately as well as the physical processes presented in its conceptual framework. The conceptualization of the aquifer to exist under both confined and unconfined conditions can be adequately described in the model. Water balance from the model shows that river to aquifer flow dominates aquifer recharge processes, and its magnitude is limited not only by relative head difference, but also by the transmissivity and hydraulic gradient of the aquifer.